Association between hemoglobin dynamic trajectories and 28-day mortality in elderly patients with sepsis: A retrospective cohort study using the MIMIC-IV database - Yan Zeng; Jun Wang; Caoyi Liu; Jingwei Zhang (PLoS ONE, 2026)
Background Anemia is a common complication in sepsis and is associated with poor prognosis. However, there are few studies on the dynamic changes in hemoglobin (Hb) levels and their relationship with prognosis in elderly patients with sepsis. This study aims to retrospectively investigate the relationship between Hb trajectories and 28-day mortality in this population. Methods This retrospective observational study used data from 4,961 elderly patients with sepsis extracted from the MIMIC-IV database(2008–2019). Hb trajectories were identified using a Joint Latent Class Model (JLCM) for longitudinal pattern classification. Following validation of proportional hazards assumptions (Schoenfeld residual test), we assessed the prognostic relationship between Hb trajectories and 28-day mortality using multivariable Cox regression models and Kaplan-Meier survival curves. Sensitivity analyses included sex-stratified multivariable Cox regression, subgroup analysis, and E-value assessment. Results Hb trajectories were classified into three patterns: Class 1 with persistently low levels, Class 2 with medium levels and a gradual decline, and Class 3 with a rapid decline from higher levels. Using Class 2 as the reference, multivariable Cox regression showed that Class 1 (HR = 1.38, 95% CI = 1.18–1.62, p < 0.001) and Class 3 (HR = 1.21, 95% CI = 1.03–1.42, p = 0.020) were associated with higher 28-day mortality. Kaplan-Meier curves indicated the lowest survival probability in Class 1 and the highest in Class 2. Gender-specific analysis revealed consistent trajectory patterns between males and females, but higher Hb values in males. The predictive power of the rapid decline pattern for early mortality was stronger in males. Conclusion The Hb trajectories in elderly sepsis patients are significantly associated with early mortality. Persistently low levels and rapid declines in Hb are indicators of poor prognosis.